ANALISIS FREE CASH FLOW, PROFITABILITAS, DEVIDEN DAN UKURAN PERUSAHAAN TERHADAP LEVERAGE PERUSAHAAN DENGAN INVESMENT OPPORTUNITY SET SEBAGAI VARIABEL MODERATING PADA SEKTOR TRADE, SERVICE & INVESMENT YANG TERDAFTAR PADA BEI - Marlina Marlina; Muhammad Rivandi (JURNAL PUNDI, 2019)
ABSTRACK The decline in the purchasing power of the public, as seen from the decline in the growth of Trade, Services and Investment sector in the retail sector subsector Retail sub-sector condition has been 2.5 years underperformance This study aims to test whether the influence of Investment Opportunity Set (IOS) free cash flow and profitability to leverage. Population in this research is Trade Company, Services & Investment, retail subsector, which is listed on BEI. period 2014-2016, ie as many as 23 Companies. Using the technique of porposive sampling, the sample in this study were 15 companies. Data analysis technique that is regersion analysis by using moderating variable. From the test results, showed that the Free cash flow has a significant effect on leverage, which is indicated from the significance value> 0.05 is 0.018. Profitability has a significant effect on firm leverage which is shown from significance value> 0.05 ie 0.000. IOS does not affect the relationship between free cash flow and leverage, as indicated by the significance value of IOS interaction with free cash flow <0.05 is 0.053. And IOS Set affects the relationship between Profitability with leverage shown from the significance value of IOS interaction with Profitability> 0.05 is 0.044 Keywords: free cash flow, profitability, leverage, IOS